2005
DOI: 10.1085/jgp.200409173
|View full text |Cite
|
Sign up to set email alerts
|

Increased Excitability of Acidified Skeletal Muscle

Abstract: Generation of the action potentials (AP) necessary to activate skeletal muscle fibers requires that inward membrane currents exceed outward currents and thereby depolarize the fibers to the voltage threshold for AP generation. Excitability therefore depends on both excitatory Na+ currents and inhibitory K+ and Cl− currents. During intensive exercise, active muscle loses K+ and extracellular K+ ([K+]o) increases. Since high [K+]o leads to depolarization and ensuing inactivation of voltage-gated Na+ channels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
174
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(188 citation statements)
references
References 38 publications
10
174
2
2
Order By: Relevance
“…31 In addition, higher metabolism in the periphery during night sweats could lead to a build-up of lactic acid in the muscles, which leads to an increased excitability of nervemuscle plates and to more frequent PLMs. 32 Although PLMs were significantly associated with vasomotor symptoms in the present study, no such association was found in women with PLM arousals. It is likely that the current study simply did not contain enough women with PLM arousals to reveal significant associations with menopause and/ or vasomotor symptoms (indicating a type II error).…”
Section: Discussioncontrasting
confidence: 75%
“…31 In addition, higher metabolism in the periphery during night sweats could lead to a build-up of lactic acid in the muscles, which leads to an increased excitability of nervemuscle plates and to more frequent PLMs. 32 Although PLMs were significantly associated with vasomotor symptoms in the present study, no such association was found in women with PLM arousals. It is likely that the current study simply did not contain enough women with PLM arousals to reveal significant associations with menopause and/ or vasomotor symptoms (indicating a type II error).…”
Section: Discussioncontrasting
confidence: 75%
“…In our experiments, with 5 mM ATP, the normal level in resting or moderately exercising muscle, a reduction of pH i of this magnitude markedly shifted the voltage dependence of ClC-1 common gating to more positive potentials, inhibiting ClC-1 activity by reducing its open probability across the physiological voltage range. Inhibition of ClC-1 by low intracellular pH in the presence of ATP is therefore likely to be the molecular mechanism underlying the reduction in sarcolemmal chloride conductance with acidosis that leads to increased membrane excitability (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Acidification has been shown to result in recovery of muscle excitability and force when these have decreased due to elevated extracellular [K ϩ ] (9). More recent studies have shown that increased excitability at low intracellular pH (pH i ) is due to reduced chloride conductance of the muscle membrane (10,11). Low pH has long been known to reduce G Cl in muscle membranes (12,13), but previous studies of the pH sensitivity of recombinantly expressed ClC-1 have failed to reconcile the reduction of G Cl of the membrane with a molecular mechanism acting directly on ClC-1.…”
mentioning
confidence: 99%
“…In the resting state, Cl 2 permeability largely exceeds that of K + (Palade and Barchi, 1977;Pedersen et al, 2009a;Pedersen et al, 2005;Pedersen et al, 2009b) and plays a major role in the maintenance of resting membrane potential (E m ). For example, when [K + ] e increases, the resulting membrane depolarization is slower and smaller when Cl 2 is present in the muscle bathing solution than in its complete absence (Dulhunty, 1978 (Pedersen et al, 2005). Reducing Cl 2 permeability by 50% allows for a recovery of membrane excitability; the number of fibers generating action potentials increases to 95% and action potential peak reaches +10 mV.…”
Section: Regulation and Impact Of The Clc-1mentioning
confidence: 99%
“…Lowering Cl 2 permeability by closing Cl 2 channels lowers Cl 2 influx, thus diminishing its ability to counteract the Na + depolarization and allowing for greater action potential amplitude. Associated with the increase in membrane excitability is an increase in force production (Pedersen et al, 2005 Regulation of excitation-contraction coupling in fatigue 2109 channels are closed improves membrane excitability and force generation.…”
Section: Regulation and Impact Of The Clc-1mentioning
confidence: 99%